SURFACE AREA AND VOLUME OF A PYRAMID (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
The pyramid is a polyhedron that has a square or triangular base and four triangular faces that meet at a common apex. Understanding the surface area and volume of a pyramid is essential in fields like geometry, architecture, and engineering. This article explores the formulae used to calculate the surface area and volume of pyramids, their derivations, and their applications. We also discuss different types of pyramids and their geometrical properties.